Kahoot! and Foreign Language Learning: A Study of Perception in a Military Context - Regina Priscylia Siswadie; Lea Santiar (JOLLT Journal of Languages and Language Teaching, 2026)
The formal and structured nature of the military environment, coupled with mission-oriented learning objectives, often results in foreign language learning being less appealing to soldiers. These conditions require pedagogical innovations that can improve learning effectiveness without neglecting military educational values and culture. This study aims to explore teachers' and students' perceptions of the use of the Kahoot! gamification platform and identify challenges in its implementation in foreign language learning at the Indonesian Army's General Military Education Center (Pusdikpengmilum). This study uses a qualitative case study approach. Data were collected through semi-structured interviews with five teachers and ten students, and reinforced with questionnaires as a triangulation technique. The results show that teachers and students have very positive perceptions of the use of Kahoot!. Based on the Technology Acceptance Model (TAM), Kahoot! is considered useful in increasing motivation, engagement, and understanding of material, as well as being easy to use in the learning process. However, the implementation of Kahoot! faces several challenges, including technical and infrastructure constraints such as internet instability, limited technological competence among some teachers, and pedagogical challenges in managing the dynamics of competition in the classroom. This study concludes that Kahoot! is a relevant and effective learning medium in a military environment. The implications of the study emphasize the importance of institutional support in the form of providing reliable technological infrastructure and ongoing training for teachers so that gamification-based learning innovations can be implemented optimally and sustainably.